Application of a Simple, Low-Cost, Low-Tech Method to Monitor Intertidal Rocky Shore Assemblages on a Broad Geographic Scale - Livore, Juan Pablo; Mendez, María M.; Klein, Eduardo; Arribas, Lorena; Bigatti, Gregorio (Frontiers in Marine Science, 2021)
Identifying susceptible regions where biodiversity changes occur at fast rates is essential in order to protect and ameliorate affected areas. Large-scale coastal monitoring programs that focus on long-term variability are scarce, yet the Marine Biodiversity Observation Network Pole to Pole is currently developing a regional collaboration throughout the American continent collecting biodiversity data in coastal habitats with a standardized systematic protocol. The use of photographic methods to collect assemblage data on intertidal rocky shores can be appropriate. The goal of this study was to analyze the performance of a simple, low-cost, non-destructive and low-tech photographic method on a broad geographical scale (∼ 2,000 km) of Atlantic Patagonian coastline. Concurrently, we aimed to identify indicators whose cover, presence or condition can be followed in time and used as beacons of change in biodiversity on these rocky intertidal shores. We also explored the potential relationships between assemblage structure and environmental variables, such as seascape classes. We identified and propose cover of mytilids, Corallina spp. and bare substrate as indicators of change due to their ecological relevance in intertidal assemblages and their visible and rapid response to human stressors or changes in environmental conditions. Finally, we illustrate the practicality and usefulness of remotely accessible environmental data, for instance the seascape classes approach as an integrative tool for large-scale rocky shore studies.